Assessing the Amount of Quadruplex Structures Present within G(2)-Tract Synthetic Random-Sequence DNA Libraries - McManus, Simon A. (Public Library of Science, 2013)
The process of in vitro selection has led to the discovery of many aptamers with potential to be developed into inhibitors and biosensors, but problems in isolating aptamers against certain targets with desired affinity and specificity still remain. One possible improvement is to use libraries enhanced for motifs repeatedly isolated in aptamer molecules. One such frequently observed motif is the two-tiered guanine quadruplex. In this study we investigated whether DNA libraries could be designed to contain a large fraction of molecules capable of folding into two-tiered guanine quadruplexes. Using comprehensive circular dichroism analysis, we found that DNA libraries could be designed to contain a large proportion of sequences that adopt guanine quadruplex structures. Analysis of individual sequences from a small library revealed a mixture of quadruplexes of different topologies providing the diversity desired for an in vitro selection. We also found that primer-binding sites are detrimental to quadruplex formation and devised a method for post-selection amplification of primer-less quadruplex libraries. With the development of guanine quadruplex enriched DNA libraries, it should be possible to improve the chances of isolating aptamers that utilize a quadruplex scaffold and enhance the success of in vitro selection experiments.